Edukasi Menyusun Menu Makanan Bergizi Seimbang saat Puasa sesuai Isi Piringku pada Ibu - Ibu Dasawisma Bougenvil Kelurahan Pelambuan Banjarmasin - Inayah, Husnul Khatimatun; Widyarni, Netty Ari; Octaviana, Elsi Setiandari Lely; Ariyanto, Edy (Universitas Baiturrahim, 2024)
Fasting is believed to have many benefits, both physical and non-physical.. In developed countries, fasting is used as a therapy (fasting therapy) to cure several degenerative diseases. The habit of people in the city of Banjarmasin during fasting is that various foods are sold at the Traditional market once a year. Almost all of the food sold there contains high levels of fat and sugar which results in increased symptoms of degenerative diseases such as cholesterol, high blood pressure and diabetes mellitus. This community service aims to ensure that mothers understand and realize the importance of balanced nutrition according to the contents of my plate to reduce the risk of degenerative diseases. The method for implementing this activity is in the form of a pretest, counseling on a balanced nutritional menu according to the contents of my plate when fasting and posttest. The final result of implementing this activity was an increase in knowledge and understanding of a balanced nutritional menu according to the contents of my plate during fasting, which can be seen from the comparison between the average pretest and posttest scores. Conclusion The understanding of mothers in Gang Gang Purnawirawan RT 2, Pelambuan sub-district can be increased through providing education and counseling about a balanced nutritional menu according to the contents of my plate when fasting